SpbR controls lipoteichoic acid length by directly inhibiting signal peptidase SpsB in Staphylococcus aureus - Youngseon Park; Tyler A. Sisley; Madeleine C. Stone; Rebecca M. Corrigan; Christopher R. Vickery; Angelika Gründling; Suzanne Walker (Proceedings of the National Academy of Sciences, 2025)
Staphylococcus aureus is a Gram-positive pathogen that causes life-threatening infections. Its cell envelope contains anionic polymers called teichoic acids that are required for cell viability. Teichoic acids come in two forms and are made by different biosynthetic pathways. One form, lipoteichoic acid (LTA), is anchored in the cell membrane; the other form, wall teichoic acid (WTA), is covalently linked to the peptidoglycan cell wall. Although the LTA and WTA biosynthetic pathways have been characterized, regulation of teichoic acid production is not well understood. Here, we identified SpbR ( SAOUHSC_00965 ), a polytopic membrane protein similar to a eukaryotic CAAX protease, as a factor that controls LTA levels in S. aureus cells. We show that loss of SpbR results in short LTAs and a synthetically sick phenotype when WTA biosynthesis is prevented, whereas overexpressing SpbR results in elongated LTAs. Mechanistically, we find that SpbR physically associates with the type I signal peptidase SpsB, which cleaves LtaS, the polymerase that assembles LTA on the extracellular side of the membrane, and we show that this physical interaction inhibits SpsB cleavage of LtaS both in vivo and in vitro. Although the phenotypes investigated here are dominated by SpbR’s effects on LtaS, it also inhibits cleavage of other SpsB substrates. Based on its role in regulating the activity of SpsB, we named this factor SpbR ( S ignal p eptidase b R egulator).